(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
In order to improve one’s overall well-being, these psychological treatments aim to do many things. The study’s goal was to determine whether and how stress-reduction programmes at Osmania University improved students’ mental health and school performance. A control group and pre- and post-tests were part of the quasi-experimental methodology used. This is why we split 40 students from Tehran’s Osmania University into two groups, an experimental group and a control group, using a convenience sampling technique. “Both groups were given a pre-test consisting of 84 questions on mental health and academic vigour using two separate questionnaires. Then, the test group participated in 10 sessions of stress management training while the control group got no treatment. After collecting post-test results from both groups, we examined them using descriptive and inferential statistics in SPSS-26.The results demonstrated that students’ academic liveliness and psychological well-being improved considerably after receiving training in stress management skills (p 0.001).This research indicated that teaching the skills for dealing with stress was an effective technique to help students exposed to high stress and pressure due to its high efficiency, especially when held in groups, its cheap cost, and its acceptability by the people.